Surface Roughness Modeling of Material Extrusion PLA Flat Surfaces - Kaltrine Jakupi; Vladimir Dukovski; Gezim Hodolli (International Journal of Polymer Science)
Complex forms may be easily created with additive manufacturing methods, but managing surface roughness remains a difficulty, even for flat surfaces, because surface quality is dependent on numerous parameters. This research investigates the effect of some printing factors on surface roughness in 3D printing methods. The purpose of this study is to quantify the most influential input printing factors on surface roughness in 3D printing processes. Polyacrylic acid thermoplastic was used to print workpieces, and mathematical models were generated using the regression method to analyze the relationship between process parameters and surface roughness. The exponential model fits the experimental data slightly better than the linear model. Only Ra-90 met all surface roughness classification requirements, while surface roughness measurements in the 0 and 45-degree directions did not meet the requirements and cannot be used to describe the surface roughness. The study highlights the importance of considering input printing parameters when optimizing surface roughness in 3D printing processes, providing valuable insights into the impact of process parameters on surface roughness.